Asthma Cases Attributable to Atopy: Results from the Third National Health and Nutrition Examination Survey - Arbes, Samuel J. (2007)
BACKGROUND: The percentage of asthma cases attributable to atopy is the subject of debate. OBJECTIVES: The objectives were to estimate the percentage of asthma cases in the U.S. population attributable to atopy and to examine associations between allergen-specific skin tests and asthma. METHODS: Data were obtained from NHANES III in which subjects aged 6–59 years were skin tested with 10 allergens. Atopy was defined as at least one positive allergen-specific test. Doctor-diagnosed current asthma was assessed by questionnaire. RESULTS: In the U.S., 56.3% of the asthma cases were attributable to atopy, and that percentage was greater among males than females, among persons in the highest education category than in lower education categories, and among persons living in highly populated metropolitan areas than in all other areas. Each allergen-specific test was strongly associated with asthma before adjustment (odds ratios varied from 2.1 to 4.5); however, after adjustment by all the allergens, only tests to cat, Alternaria, white oak, and perennial rye were independently associated with asthma. Perennial rye was inversely associated with asthma. Of the 10 allergens, a positive response to cat accounted for the highest percentage of asthma cases (29.3%). CONCLUSIONS: About half of the current asthma cases in the U.S. population represented by NHANES III were attributable to atopy. Some allergen-specific skin tests were not independently associated with asthma. CLINICAL IMPLICATIONS: If atopy could be prevented or reversed, or its effect on asthma blocked, then a large percentage of asthma cases in the U.S. population could be prevented.